The Development of Islamic Accounting and Its Relevance to the Development of the Islamic Financial Industry in Indonesia After the Covid-19 Pandemic - Rozi Andrini (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
After the Covid-19 pandemic had many impacts on Indonesia, ranging from health impacts to the economy, including the Islamic finance industry. Many loss events occurred, such as payment arrears to default on the effects of Covid-19. The government has issued various policies to stimulate the economic impact. The Indonesian Institute of Accountants considers this impact on the application of Financial Accounting Standards to sharia commercial transactions in Islamic financial institutions. This paper aims to analyze the development of Islamic accounting and its relevance to the development of the Islamic finance industry after the Covid-19 pandemic. This type of research is library research (library research) by analyzing sources in the form of books, articles and regulations related to sharia accounting and the sharia finance industry. The results showed that in terms of regulations in Indonesia, sharia accounting began to be regulated in 2002 with the passing of the Financial Accounting Standards Guidelines (PSAK) No. 59 and the Indonesian Sharia Banking Accounting Guidelines (PAPSI). Then in order to be able to answer the need for accounting standards for Islamic financial institutions other than Islamic banking, PSAK 101-106 was passed in 2007, followed by the submission of draft PSAK 107-109 in 2008, and in 2018 PSAK 112 was passed which only became effective in 2021. Developments in sharia accounting are currently relevant to developments in the sharia financial industry. This is because the development of sharia accounting is heavily influenced by the development of the sharia financial industry, especially sharia banking. The financial industry whose operations are based on sharia principles must implement standardized recording, namely the sharia Financial Accounting Standard Statement (PSAK) stipulated by the Sharia Accounting Board of the Indonesian Accountants Association (DSAS-IAI). After the Covid-19 pandemic, IAI continued to accommodate accounting interests for the Islamic finance industry. Beginning of 2020 PSAK 102: Accounting for Murabahah (revised 2019), ISAK 101: Recognition of Tangible Murabahah Income Without Significant Risk Related to Ownership of Inventory and ISAK 102: Impairment of Murabahah Receivables takes effect in early 2020. DSAS-IAI decided to provide guidance on implementationincurred loss model in ISAK 102 regarding the impact of the covid-19 pandemic. It is hoped that this paper can contribute to the analysis of the development of Islamic accounting and its relevance to the development of the Islamic finance industry after the Covid-19 pandemic.